Legal Review In Structuring And Normalization Of Rivers As An Effort To Mitigate Flooding In The City Of Banjarmasin - Hadin Muhjad, Muhammad; Erfa Redhani, Muhammad; Anwary, Ichsan; Fikri Hadin, Ahmad (International Journal of Educational Research & Social Sciences, 2022)
The rivers and canals in Banjarmasin need to be reorganized to restore the rivers and canals to be able to function. Various legal policies have been taken by Banjarmasin Government, from issuing regulations on rivers to making policies to establish a River Normalization Task Force. This research is aimed to analyze the Banjarmasin government's regional regulations that regulate the rivers and rivers layout, as well as the effectiveness of the legal policy taken by the government as mitigation of the flood problems Banjarmasin faces.This study uses an interdisciplinary legal research method (socio-legal methodology); where the law (in this case the statutory text) is not only interpreted as an object of value-free study but the law is interpreted as an object that is rich in values (including non-legal values).Based on the geographical condition ofBanjarmasin, rivers and canals should be very important for Banjarmasin as a way to avoid flooding. Therefore, it is necessary to arrange rivers and canals in Banjarmasin comprehensively and this arrangement cannot be done only partially. The river arrangement includes regulatory, institutional, and community development aspects in the vicinity. The development of the city of Banjarmasin from the point of view of city development must start from the rivers.